Sodium alginate–silica composite aerogels from rice husk ash for efficient absorption of organic pollutants. (April 2022) - Han, Xinhong; Liang, Jiacheng; Fukuda, Suneerat; Zhu, Lingjun; Wang, Shurong
Abstract: Sodium alginate–silica (SAS) composite aerogels with excellent absorption capacity were synthesized from rice husk ash through a sol-gel process and freeze drying. The physical and chemical properties of the SAS aerogels were fully characterized using field emission scanning electron microscopy, N2 adsorption–desorption isotherms, thermogravimetric analysis, Fourier transform infrared spectroscopy, and other techniques. The silica-based composite aerogel containing 18% sodium alginate (18-SAS) had the largest specific surface area of 205.1 m 2 g −1, the highest pore volume of 0.953 cm 3 g −1, and the maximum organic-solvent absorption capacity of 6–14 g g −1 . Such an environmentally friendly, low-cost aerogel material with excellent performance is a promising candidate for organic-pollutant absorption. Highlights: Hydrophobic silica-based composite aerogels with a silicon source of rice husk ash were synthesized. Natural sodium alginate was chosen as the reinforcing agent. The hydrophobic sodium alginate–silica composite aerogels showed excellent organic-solvent absorption capacity.